Zirconium in the Nuclear Industry: 18th International Symposium 2018
DOI: 10.1520/stp159720160069
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Zirconium Oxide Microstructure on Corrosion Performance: A Comparison between Neutron, Proton, and Nonirradiated Oxides

Abstract: Automated crystal orientation mapping in the transmission electron microscope has been used to simultaneously map the phase, orientation and grain morphology of oxides formed on Zircaloy-2 after 3 and 6 cycles in a BWR reactor in unprecedented detail. For comparison, a region of a pre-oxidised autoclave-formed oxide was also proton irradiated at the Dalton Cumbrian Facility. The proton irradiation was observed to cause additional stabilisation of the tetragonal phase, attributed to the stabilising effect of ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
4
3
0
Order By: Relevance
“…3(e) for these three materials. More than 50% of the indexed m-ZrO2 grains are observed to have (104 ̅ ) m-ZrO2 lying within 30° of the surface normal, in good agreement with previous normal EBSD [37] and ASTAR [59] results. The colour in the orientation maps changes gradually with depth in the oxide, with a strong texture in the outer few microns that decreases in strength towards the oxide/metal interface.…”
Section: Bulk Oxide Texture Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…3(e) for these three materials. More than 50% of the indexed m-ZrO2 grains are observed to have (104 ̅ ) m-ZrO2 lying within 30° of the surface normal, in good agreement with previous normal EBSD [37] and ASTAR [59] results. The colour in the orientation maps changes gradually with depth in the oxide, with a strong texture in the outer few microns that decreases in strength towards the oxide/metal interface.…”
Section: Bulk Oxide Texture Analysissupporting
confidence: 90%
“…A small volume fraction of equiaxed t-ZrO2 grains are found scattered throughout the oxide layers. [59] . The grain size of the tetragonal phase is similar on all three alloys, but the values of tetragonal phase fraction are significantly lower than reported by bulk measurement techniques, laboratory and synchrotron XRD for example, where analysis of oxide layers formed on similar alloys reported the tetragonal phase fraction to lie in the range 3-15% [60][61][62][63].…”
Section: Oxide Phase Distribution and Grain Morphologymentioning
confidence: 99%
“…Similar observation is seen in proton irradiated Zircaloy-2 [65]. Garner et al [65] studied neutron irradiated Zircaloy-2, revealed no extra stabilisation of the tetragonal grains which was attributed to the faster oxide growth and low total irradiation damage.…”
Section: Damage To the Oxidesupporting
confidence: 55%
“…Similar observation is seen in proton irradiated Zircaloy-2 [65]. Garner et al [65] studied neutron irradiated Zircaloy-2, revealed no extra stabilisation of the tetragonal grains which was attributed to the faster oxide growth and low total irradiation damage. This is not contradictory to our findings since Zr-1.0Nb has slower oxide growth than the Zircaloy-2 samples, so that longer total damage time in our Zr-1.0Nb gives enough time to introduce more tetragonal phase.…”
Section: Damage To the Oxidesupporting
confidence: 55%
“…In this study, the zirconium oxides grown by autoclave corrosion were observed to have a high resistance to irradiation-induced amorphisation up to a fluence of 1.9 × 10 16 ions.cm -2 at 10 12 ions.cm -2 .s -1 , but a gradual evolution of microstructure in the bulk oxide can be seen in long term in-situ irradiation experiments as shown in Figure 3. Strong diffraction contrast can be seen in the pre-irradiation sample, Figure 3 (a), arising from the characteristic nanocrystalline grain structure in a corrosion scale grown under simulated reactor conditions, and the complex SAD patterns are also characteristic of the textured zirconium oxide layer [69,70]. The diffraction contrast in the bright-field micrographs gradually changed under irradiation and we observed fewer but brighter spots in the diffraction patterns.…”
Section: In-situ Observation Of Irradiation-induced Phase Transformationmentioning
confidence: 76%